The older sibling effect: comparing social functioning outcomes for autistic children with typically developing siblings, no siblings, and autistic siblings - Rum, Yonat; Dolev, Adi; Reichmann, Ofri; Zachor, Ditza A.; Avni, Einat; Ilan, Michal; Meiri, Gal; Koller, Judah (Frontiers in Psychology, 2025)
BackgroundPrevious research showed that having older, typically developing (TD) siblings is associated with better social functioning in autistic children. Modeling by older siblings and the fact that siblings provide a social companion to practice social skills were suggested as explanations.ObjectivesTo investigate whether having older autistic siblings is associated with a similar or an opposite pattern.MethodsThe Azrieli National Centre for Autism and Neurodevelopment Research in Israel database was used to retrieve data of autistic children who completed the Autism Diagnostic Observation Scale [ADOS-2] for secondary analyses. A cohort of 1,100 children was scanned to identify autistic children with no siblings (No-Sib; n = 146), older TD siblings (Older-TD-Sib; n = 300), and older autistic siblings (Older-Autistic-Sib; n = 40). Each Older-Autistic-Sib child was matched to (1) Older-TD-Sib, and (2) No-Sib, by sex, age, and cognitive scores, resulting in 29 triads of matched participants (N = 87). The three groups were compared on the ADOS-2 Social Affect sub-domain [a lower score (0–10) indicates less severe social-communication symptoms (better social functioning)].ResultsGroup comparisons revealed that autistic children with older TD siblings showed better social functioning than those with no siblings (p = 0.002, adjusted p = 0.007, d = 0.62). Autistic children with older autistic siblings showed a similar but weaker trend compared to those with no siblings (p = 0.082, adjusted p = 0.247, d = 0.40), and no difference was found between children with older TD versus autistic siblings (p = 0.647, d = −0.13; BF₀₁ = 4.55).ConclusionAutistic children with autistic siblings demonstrated an “intermediate pattern,” implying a possible positive effect of having an older autistic sibling on social functioning, similar to that of having an older TD sibling, albeit smaller. This could be explained by complex relationships between sibling modeling and companionship or the impact of parenting measures, such as experience. These speculative explanations should be directly examined in future research.